PENGARUH KONSENTRASI GELATIN TERHADAP SIFAT ORGANOLEPTIK PERMEN JELLY SUSU KAMBING - Eletra, Yuka; -, Susilawati; Astuti, Sussi (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
This research was conducted to find out the effect of gelatin concentration on the sensory characteristic of goat milk jelly candy.  The research was designed using a Completely Randomized Block Design with gelatin concentration as a single factor consisting of five levels, namely 5%, 10%, 15%, 20%, and 25%. The research was repeated 5 times.   Data were analyzed with Analysis of Varians to find out the treatment effects, then continued tested using Least Significant Difference (LSD) test to find out the best treatment which was determined by the highest score of flavor, elasticity, color, and overall acceptance.  Chemical composition analysis was conducted on the best treatment product. The result showed that gelatin concentration had significant effect on flavor and highly significant effect on elasticity, color, and overall acceptance of the goat milk jelly candy.  The best treatment was gelatin addition at a concentration of 10%.  The candy had a flavor score of 3.35 (rather typical of goat milk), an elasticity score of 3.55 (elastic), and hedonic score for color of 3.66 (like) and an overall acceptance of 3.73 (like). Its water, ash, reduced sugar, protein, and fat contents were 18.01%, 1.60%, 13.56%, 5.65%, and 0.21%, respectively. Keywords: gelatin, goat milk, jelly candy.